A Comparative Study of Self-Efficacy from the Perspective of the Qur'an and Psychology - Reza Shokrani; Vahid Salimi; Amir Ghamarani (آموزه‌های قرآنی)
Self-efficacy means: A person’s beliefs or judgments about his or her ability to perform duties and responsibilities. This concept is one of the concepts that psychologists have achieved through the study of human characteristics and through experimental (empirical) studies. In this article, it is tried to re-read this concept from the perspective of the Qur'an and to compare it in the Qur'an and psychology. It became clear by examining all the verses of the Holy Qur'an, that the Qur'an believes in human abilities as a principle on the path to perfection and has raised this issue in some verses. It was found that in the verses of the Qur'an by comparing the concept of self-efficacy in the Qur'an and psychology in addition to what is said in the field of psychology about self-efficacy, other sources and factors are addressed. In the present study, the sources of self-efficacy that are confirmed from the perspective of the Qur'an are listed in two parts: (1) Verses from the Qur'an that confirm the sources of self-efficacy from a psychological point of view, (2) Sources of self-efficacy that are specifically stated in the Qur'an. There are also differences in the creation and formation of self-efficacy from the perspective of the Qur'an and psychology.